Statement on the confirmatory data following the Article 12 MRL review for triclopyr - European Food Safety Authority (EFSA) (EFSA Journal)
Abstract In accordance with Article 31 of Regulation (EC) No 178/2002, EFSA received a mandate from the European Commission to issue a scientific statement concerning the confirmatory data following the review of the existing maximum residue levels (MRLs) under Article 12 of Regulation (EC) No 396/2005 for triclopyr. Although the required application in support to the confirmatory data following the MRL review was not submitted within deadline, some information identified as unavailable in the MRL review has been made available to EFSA in the context of other applications submitted under different regulatory processes. Based on the assessment of the available data, EFSA concluded that the tentative MRL for apples, pears and peaches is confirmed. The tentative MRLs for grapefruits, oranges, lemons, mandarins, apricots and rice are not fully supported by data. Risk manager may consider the alternative MRL of 0.07 mg/kg for oranges, lemons, mandarins and the lowering to the specific limit of quantification (LOQ) for grapefruits, apricots and rice. An update of the consumer risk assessment for triclopyr was performed and it did not indicate any potential consumer health risks. The statement was circulated to Member States for consultation via a written procedure before finalisation.